Teaching Vocabulary Acquisition through Derivational Suffixes of SMP Santo Petrus Medan in the Academic Year 2017/2018 - Karisma Erikson Tarigan; Margaret Stevani (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study is aimed to improve the students’ vocabulary acquisition through derivational suffixes strategy. The subject of this study is the students of Class IX-1 of SMP Santo Petrus Medan in the academic year of 2017/2018. This study is conducted by applying Classroom Action Research (CAR), which have been conducted in two cycles (cycle 1 and cycle 2) and each cycle consisted of four meetings. The results of vocabulary test shows that the progressing mean score of the pretest is 34.66, post test in cycle 1 is 93.46, and post test in cycle 2 is 97.33. In cycle 1, the comparison percentage of nominal is 88.83%, verbal is 77.46%, adjectival is 40.74%, and adverbial is 84.14%. In cycle 2, the comparison percentage of nominal is 100%, verbal is 95.45%, adjectival is 65.84%, and adverbial is 94.91%. The percentage of the students who pass Minimal Criterion Mastery in each cycle is 100%, with the improvement 169.64% in cycle 1 to 180.81% in cycle 2. These indicate that there is a significant improvement of the students’ vocabulary mastery through affixation strategy of Class IX-1 of SMP Santo Petrus Medan in the academic year of 2017/2018.